Exploring Parental Perceptions and Concerns About Sexuality and Reproductive Health of Their Child With Intellectual and Developmental Disability (IDD) in Mumbai - Menon, Pooja; Sivakami, Muthusamy (Frontiers in Sociology, 2019)
In India, sexuality is defined by society, which considers it as a taboo and is usually restricted to sex and related issues like sexual abuse, safe sex, unwanted pregnancy, etc. For a person with disability, sexual desires and wish for parenthood are considered as uncommon. Persons with intellectual and developmental disability (IDD) are characterized by subnormal intelligence, which may partially or totally restrict the person's ability to perform day-to-day activities and take life decisions. Thus, perceptions of primary caregivers, who take decisions on behalf of the person with IDD, have an important role in their life. The aim of the study is to understand parents' perceptions and concerns about the sexuality and reproductive health of their child with an IDD. The study adopted a qualitative methodology wherein 14 primary caregivers of individuals with IDD belonging to different socio-economic and demographic backgrounds were interviewed in Mumbai. The common perceptions were that puberty is expected, sexual behavior is unexpected, and there is a hope for cure. The reaction to puberty onset appeared to vary with the gender of the child. Puberty onset was often seen as an enabling factor for marriage especially among parents of female child. Marriage and/or childbirth was perceived as a possible cure for IDD by some parents. The dominant parental concerns were found to be safety, early onset of puberty, perception of child's action by others, and concerns about the child's family life. These concerns were also found to vary with the gender of the child, type of disability, and the socio-economic status of the family. Some of the perceptions about sexuality were shaped by the primary caregivers' concern for the individual with IDD.